WASWC News - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The World Association of Soil and Water Conservation (WASWC) founded in 1985, publishes quarterly information on advances made in soil and water conservation throughout the world. For more details, contact: WASWC, c/o SWCS 7515 NE Ankeney Road...